PENERAPAN BIMBINGAN KONSELING MEMBENTUK KARAKTER ANAK USIA DINI DI TK AN NUR SURABAYA - Herlina Widya Puspitasari; Jazilatul Athiyyah; Kartika Sari; Lailatul Masruroh; Rossy Adellia Rahma (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2023)
Counseling guidance in PAUD is very important and needed because it helps the growth and development of students both in terms of psychological, emotional, physical and thinking. PAUD is an educational institution before the elementary school level as an effort to foster and teach children from birth to the age of six in a certain way, with the aim of helping the growth and development of children both physically and spiritually so that they are ready. . continue to the next level of education on the formal track. non-formal or informal. Counseling guidance in PAUD institutions must be given to all students, not only to problem children. Because even children who have no problems need to get guidance services so that it is easier for them to develop their talents, interests and potential. Thus counseling guidance is not only to deal with problem students, but also as an action to meet the child's developmental needs to the fullest. The application of learning in early childhood education can be through the media of toys. Islamic-based guidance and counseling media for early childhood in the formation of independent character can be done with game media.